A new approach for agile teams' allocation in open innovation projects - Vitor Anes; António Abreu; Ana Dias; Jo\~ao Calado (Administrative Sciences, 2023)
Due to constant change in the marketplace, it can be difficult for companies to secure the material, human, and technological resources necessary for competitive innovation activities. In this sense, and to overcome these constraints, the open innovation model is a quite successful approach, where the sharing of resources among companies allows the formation of an innovation ecosystem. However, the execution time of these projects can be negatively affected if the performance of each work team is not taken into account. In this work, the application of the agile approach in open innovation projects is proposed as a way to reduce the uncertainty both in the execution time of the projects and in the respective implementation costs. In this sense, a methodology for optimal team assignment for agile teams in open innovation projects according to their performance on each project task is developed to determine the optimal team assignment that leads to the shortest project execution time. This methodology will support decision making in the project management of open innovation projects, especially in the selection of the internal and external work teams that will participate in a given innovation project. The application of the proposed methodology is illustrated with an example describing and analyzing the different steps of its application. The results show that with the proposed methodology it is possible to take into account the performance of each team when calculating the project execution time and that the project execution time varies depending on the assignment of the agile teams to the project tasks. It is also shown that it is possible to determine the optimal assignment with the shortest project execution time.
Keywords: 350; open innovation; agile teams; decision making; optimization; project completion time; project management; team assignment